Charlatans (Pia Grazdani, ,, 2017)
The explosive new thriller from New York Times-bestselling author and master of the medical thriller Robin Cook.   Newly minted chief resident at Boston Memorial Hospital Noah Rothauser is swamped in his new position, from managing the surgical schedules to dealing with the fallouts from patient deaths. Known for its medical advances, the famed teaching hospital has fitted several ORs as 'hybrid operating rooms of the future''an improvement that seems positive until an anesthesia error during a routine procedure results in the death of an otherwise healthy man. Noah suspects Dr. William Mason, an egotistical, world-class surgeon, of an error during the operation and of tampering with the patient's record afterward. But Mason is quick to blame anesthesiologist, Dr. Ava London. When more anesthesia-related deaths start to occur, Noah is forced to question all of the residents on his staff, including Ava, and he quickly realizes there's more to her than what he sees. A social-media junkie, Ava has created multiple alternate personas for herself on the Internet. With his own job and credibility now in jeopardy, Noah must decide which doctor is at fault and who he can believe'before any more lives are lost.

Safe haven (Distributed by Recorded Books, [Manufactured and distributed by] Findaway World, LLC, Hachette Audio, Playaway Digital Audio, Grand Central Pub, Grand Central Pub. Large Print, Grand Central Publishing, 2010)
In a small North Carolina town, a mysterious and beautiful woman running from her past slowly falls for a kind-hearted store owner . . . until dark secrets begin to threaten her new life. When a mysterious young woman named Katie appears in the small North Carolina town of Southport, her sudden arrival raises questions about her past. Beautiful yet self-effacing, Katie seems determined to avoid forming personal ties until a series of events draws her into two reluctant relationships: one with Alex, a widowed store owner with a kind heart and two young children; and another with her plainspoken single neighbor, Jo. Despite her reservations, Katie slowly begins to let down her guard, putting down roots in the close-knit community and becoming increasingly attached to Alex and his family. But even as Katie begins to fall in love, she struggles with the dark secret that still haunts and terrifies her . . . a past that set her on a fearful, shattering journey across the country, to the sheltered oasis of Southport. With Jo's empathetic and stubborn support, Katie eventually realizes that she must choose between a life of transient safety and one of riskier rewards . . . and that in the darkest hour, love is the only true safe haven.

Apples never fall (Thorndike Press large print core, ,, 2021)
#1 New York Times Bestseller ? A Peacock Original TV Series–Now Streaming! ? "Gripping."?Oprah.com ? From Liane Moriarty, the bestselling author of Big Little Lies and Nine Perfect Strangers, comes Apples Never Fall, a novel that looks at marriage, siblings, and how the people we love the most can hurt us the deepest. The Delaney family love one another dearly—it’s just that sometimes they want to murder each other . . . If your mother was missing, would you tell the police? Even if the most obvious suspect was your father? This is the dilemma facing the four grown Delaney siblings. The Delaneys are fixtures in their community. The parents, Stan and Joy, are the envy of all of their friends. They’re killers on the tennis court, and off it their chemistry is palpable. But after fifty years of marriage, they’ve finally sold their famed tennis academy and are ready to start what should be the golden years of their lives. So why are Stan and Joy so miserable? The four Delaney children—Amy, Logan, Troy, and Brooke—were tennis stars in their own right, yet as their father will tell you, none of them had what it took to go all the way. But that’s okay, now that they’re all successful grown-ups and there is the wonderful possibility of grandchildren on the horizon. One night a stranger named Savannah knocks on Stan and Joy’s door, bleeding after a fight with her boyfriend. The Delaneys are more than happy to give her the small kindness she sorely needs. If only that was all she wanted. Later, when Joy goes missing, and Savannah is nowhere to be found, the police question the one person who remains: Stan. But for someone who claims to be innocent, he, like many spouses, seems to have a lot to hide. Two of the Delaney children think their father is innocent, two are not so sure—but as the two sides square off against each other in perhaps their biggest match ever, all of the Delaneys will start to reexamine their shared family history in a very new light.

The silent patient (Thorndike Press large print basic, ,, 2019)
**THE INSTANT #1 NEW YORK TIMES BESTSELLER** "An unforgettable—and Hollywood-bound—new thriller... A mix of Hitchcockian suspense, Agatha Christie plotting, and Greek tragedy." —Entertainment Weekly The Silent Patient is a shocking psychological thriller of a woman’s act of violence against her husband—and of the therapist obsessed with uncovering her motive. Alicia Berenson’s life is seemingly perfect. A famous painter married to an in-demand fashion photographer, she lives in a grand house with big windows overlooking a park in one of London’s most desirable areas. One evening her husband Gabriel returns home late from a fashion shoot, and Alicia shoots him five times in the face, and then never speaks another word. Alicia’s refusal to talk, or give any kind of explanation, turns a domestic tragedy into something far grander, a mystery that captures the public imagination and casts Alicia into notoriety. The price of her art skyrockets, and she, the silent patient, is hidden away from the tabloids and spotlight at the Grove, a secure forensic unit in North London. Theo Faber is a criminal psychotherapist who has waited a long time for the opportunity to work with Alicia. His determination to get her to talk and unravel the mystery of why she shot her husband takes him down a twisting path into his own motivations—a search for the truth that threatens to consume him....

Maybe now (Maybe someday, 3,, 2019)
"Ridge and Sydney are thrilled to finally be together guilt-free. But Warren and Bridgette's relationship is as tumultuous as ever, and Maggie grapples with her illness. When she comes across an old list of things she wanted to do, Maggie decides to live life to the fullest and accomplish these dreams. Maggie keeps Ridge updated on her adventures, but he can't help but worry, even as Sydney grows suspicious about their friendship. But if she's going to move past this jealousy, she'll need to reconcile how she and Ridge came together with the fact that Maggie will always be in their lives ... or walk away from the man she loves"--

The swimmers (Alfred A. Knopf, Random House Large Print, Books on Tape, 2022)
NATIONAL BESTSELLER • CARNEGIE MEDAL FOR EXCELLENCE WINNER • From the award-winning author of The Buddha in the Attic and When the Emperor Was Divine comes a novel that "starts as a catalogue of spoken and unspoken rules for swimmers at an aquatic center but unfolds into a powerful story of a mother’s dementia and her daughter’s love" (The Washington Post). The swimmers are unknown to one another except through their private routines (slow lane, medium lane, fast lane) and the solace each takes in their morning or afternoon laps. But when a crack appears at the bottom of the pool, they are cast out into an unforgiving world without comfort or relief.   One of these swimmers is Alice, who is slowly losing her memory. For Alice, the pool was a final stand against the darkness of her encroaching dementia. Without the fellowship of other swimmers and the routine of her daily laps she is plunged into dislocation and chaos, swept into memories of her childhood and the Japanese American incarceration camp in which she spent the war. Alice's estranged daughter, reentering her mother's life too late, witnesses her stark and devastating decline.

Overkill (Grand Central Publishing/Hachette Book Group, Hachette Audio, Grand Central Publishing, 2022)
#1 New York Times bestselling author Sandra Brown delivers a riveting thriller in which a conflict of conscience for a former football star and an ambitious state prosecutor swiftly intensifies into a fight for their lives.   Former Super Bowl MVP quarterback Zach Bridger hasn’t seen his ex-wife, Rebecca Pratt, for some time—not since their volatile marriage imploded—so he’s shocked to receive a life-altering call about her. Rebecca has been placed on life support after a violent assault, and he—despite their divorce—has medical power-of-attorney. Zach is asked to make an impossible choice: keep her on life support or take her off of it. Buckling under the weight of the responsibility and the glare of public scrutiny, Zach ultimately walks away, letting Rebecca's parents have the final say.   Four years later, Rebecca's attacker, Eban—the scion of a wealthy family in Atlanta—gets an early release from prison. The ludicrous miscarriage of justice reeks of favoritism, and Kate Lennon, a brilliant state prosecutor, is determined to put him back behind bars. Rebecca’s parents have kept her alive all these years, but if her condition were to change—if she were to die—Eban could be retried on a new charge: murder.   It isn’t lost on Zach that in order for Eban to be charged with Rebecca’s murder, Zach must actually be the one to kill her. He rejects Kate’s legal standpoint but can’t resist their ill-timed attraction to each other. Eban, having realized the jeopardy he’s in, plots to make certain that neither Zach nor Kate lives to see the death of Rebecca—and the end of his freedom.

The alpha enigma (Team PSI, 1,, 2021)
A thrilling new science fiction mystery from the New York Times bestselling author of the Donovan novels Dr. Timothy Ryan, head of the military psychiatric unit at Grantham Barracks, is meeting a new patient, a woman known as "Prisoner Alpha." As she is being transferred, they are attacked by assassins, barely escaping with their lives. One shooter vanishes, leaving behind a dead companion unlike anyone Ryan has ever seen. But even more baffling is the puzzle of Alpha herself. She speaks in a strange tongue, and doodles in bars, dots, and little pictures like nothing Ryan has ever seen. Is she some sort of savant, or the most cunning spy he's ever met? Meanwhile, in Egypt, archaeologist Reid Farmer uncovers an 18th-Dynasty tomb that shouldn't exist, filled with Mayan epigraphy, mathematics, and materials that didn't exist 3,000 years ago. As a result of this discovery, Reid and forensic anthropologist Kilgore France—along with the sarcophagus they have found—are snatched away to a hidden lab to solve the enigma of a man lost in time. As dark forces gather, Alpha makes an impossible escape from Grantham. Ryan quickly becomes the prime suspect in her disappearance, but with a team of unique allies, sets out to prove his innocence. Together, they must find Alpha and save Ryan before it is too late.

Heavy: an American memoir (Simon & Schuster Audio, Scribner, 2018)
*Named a Best Book of 2018 by the New York Times, Publishers Weekly, NPR, Broadly, Buzzfeed (Nonfiction), The Undefeated, Library Journal (Biography/Memoirs), The Washington Post (Nonfiction), Southern Living (Southern), Entertainment Weekly, and The New York Times Critics* *WINNER of the Andrew Carnegie Medal and FINALIST for the Kirkus Prize * In this powerful and provocative memoir, genre-bending essayist and novelist Kiese Laymon explores what the weight of a lifetime of secrets, lies, and deception does to a black body, a black family, and a nation teetering on the brink of moral collapse. Kiese Laymon is a fearless writer. In his essays, personal stories combine with piercing intellect to reflect both on the state of American society and on his experiences with abuse, which conjure conflicted feelings of shame, joy, confusion and humiliation. Laymon invites us to consider the consequences of growing up in a nation wholly obsessed with progress yet wholly disinterested in the messy work of reckoning with where we’ve been. In Heavy, Laymon writes eloquently and honestly about growing up a hard-headed black son to a complicated and brilliant black mother in Jackson, Mississippi. From his early experiences of sexual violence, to his suspension from college, to his trek to New York as a young college professor, Laymon charts his complex relationship with his mother, grandmother, anorexia, obesity, sex, writing, and ultimately gambling. By attempting to name secrets and lies he and his mother spent a lifetime avoiding, Laymon asks himself, his mother, his nation, and us to confront the terrifying possibility that few in this nation actually know how to responsibly love, and even fewer want to live under the weight of actually becoming free. A personal narrative that illuminates national failures, Heavy is defiant yet vulnerable, an insightful, often comical exploration of weight, identity, art, friendship, and family that begins with a confusing childhood—and continues through twenty-five years of haunting implosions and long reverberations.
Been , Boy man. Train ; Nan ; Wet ; Be , Black abundance. Meager ; Contraction ; Hulk ; Gumption , Home worked. Fantastic ; Disaster ; Already ; Soon , Addict Americans. Greens ; Terrors ; Seat belts ; Promises , Bend.

The professor and the madman: a tale of murder, insanity, and the making of the Oxford English dictionary (Multiple titles for book club discussion groups, ,, 1998)
A fine storyteller takes on a great story: American surgeon living in London kills a stranger, judged insane, incarcerated, connects with Jas. Murray the editor of the original OED, over decades contributes 10,000 examples of usage to the great dictionary. Good description of the creation of the OED. No index. Annotation c. Book News, Inc., Portland, OR (booknews.com)
The dead of the night in Lambeth Marsh , The man who taught Latin to cattle , The madness of war , Gathering Earth's daughters , The big dictionary conceived , The scholar in cell block two , Entering the lists , Annulated, art, brick-tea, buckwheat , The meeting of minds , The unkindest cut , Then only the monuments.

Growing pangs (Random House Children's Books, 2022)
NAMED ONE OF THE BEST BOOKS OF THE YEAR BY NPR A PARENTS MAGAZINE BEST BOOK Inspired by a true story! Eleven-year old homeschooled Katie has always felt different . . . and now she can't stop worrying.  Introducing an irresistibly relatable graphic novel about friendship, anxiety, and growing up. "An excellent companion to Raina Telgemeier's Guts and Shannon Hale and LeUyen Pham's Real Friends."—Booklist, Starred Review New Friends. New grade. New worries? Katie's always felt different. She's homeschooled, she has freckles, and her teeth are really crooked. But none of these things matter to Kacey. They’re best friends forever—just like their necklaces say. But when they go to summer camp, Kacey starts acting weird. What happened to the “forever”? And when Katie gets home, she can’t stop worrying. About getting braces. About 6th grade. About friends. She knows tapping three times or opening and closing a drawer won’t make everything better . . . but sometimes it helps stop the worrying. Is something wrong with her? And will anyone want to be friends with her if they find out?

The immortal life of Henrietta Lacks (Multiple titles for book club discussion groups, ,, 2010)
#1 NEW YORK TIMES BESTSELLER • “The story of modern medicine and bioethics—and, indeed, race relations—is refracted beautifully, and movingly.”—Entertainment Weekly NOW A MAJOR MOTION PICTURE FROM HBO® STARRING OPRAH WINFREY AND ROSE BYRNE • ONE OF THE “MOST INFLUENTIAL” (CNN), “DEFINING” (LITHUB), AND “BEST” (THE PHILADELPHIA INQUIRER) BOOKS OF THE DECADE • ONE OF ESSENCE’S 50 MOST IMPACTFUL BLACK BOOKS OF THE PAST 50 YEARS • WINNER OF THE CHICAGO TRIBUNE HEARTLAND PRIZE FOR NONFICTION NAMED ONE OF THE BEST BOOKS OF THE YEAR BY The New York Times Book Review • Entertainment Weekly • O: The Oprah Magazine • NPR • Financial Times • New York • Independent (U.K.) • Times (U.K.) • Publishers Weekly • Library Journal • Kirkus Reviews • Booklist • Globe and Mail Her name was Henrietta Lacks, but scientists know her as HeLa. She was a poor Southern tobacco farmer who worked the same land as her slave ancestors, yet her cells—taken without her knowledge—became one of the most important tools in medicine: The first “immortal” human cells grown in culture, which are still alive today, though she has been dead for more than sixty years. HeLa cells were vital for developing the polio vaccine; uncovered secrets of cancer, viruses, and the atom bomb’s effects; helped lead to important advances like in vitro fertilization, cloning, and gene mapping; and have been bought and sold by the billions.  Yet Henrietta Lacks remains virtually unknown, buried in an unmarked grave. Henrietta’s family did not learn of her “immortality” until more than twenty years after her death, when scientists investigating HeLa began using her husband and children in research without informed consent. And though the cells had launched a multimillion-dollar industry that sells human biological materials, her family never saw any of the profits. As Rebecca Skloot so brilliantly shows, the story of the Lacks family—past and present—is inextricably connected to the dark history of experimentation on African Americans, the birth of bioethics, and the legal battles over whether we control the stuff we are made of.  Over the decade it took to uncover this story, Rebecca became enmeshed in the lives of the Lacks family—especially Henrietta’s daughter Deborah. Deborah was consumed with questions: Had scientists cloned her mother? Had they killed her to harvest her cells? And if her mother was so important to medicine, why couldn’t her children afford health insurance?  Intimate in feeling, astonishing in scope, and impossible to put down, The Immortal Life of Henrietta Lacks captures the beauty and drama of scientific discovery, as well as its human consequences.

The professor and the madman (HarperAudio, Harper Audio, 2005)
National Bestseller! One of the greatest literary achievements in the history of English letters, the creation of the Oxford English Dictionary began in 1857, took seventy years to complete, and drew from tens of thousands of brilliant minds. But hidden within the rituals of its creation is a fascinating and mysterious story. Professor James Murray was the distinguished editor of the OED project. Dr. William Chester Minor, an American surgeon who had served in the Civil War, was one of thousands of contributors to the dictionary. But Minor was no ordinary contributor. He was remarkably prolific, sending thousands of neat, hand-written quotations from his home. On numerous occasions Murray invited Minor to visit Oxford and celebrate his work, but Murray's offer was regularly, mysteriously, refused. Finally, a puzzled Murray set out to visit him. It was then that Murray would finally learn the truth about Minor . . . that, in addition to being a masterly wordsmith, Minor was also a murderer, clinically insane - and locked up in Broadmoor, England's harshest asylum for criminal lunatics. The Professor and the Madman is an extraordinary tale of madness and genius, and the incredible obsessions of two men at the heart of the Oxford English Dictionary and literary history. Written with riveting insight and detail, Simon Winchester delivers a fascinating glimpse into one man's tortured mind and his contribution to another man's magnificent dictionary.